Exploring Freehand Drawing Skills of Engineering Students as a Support of Visualization - Alfonso Martín Erro; María Luisa Martínez Muneta; Ángel Antonio Rodríguez Sevillano (MDPI AG, 2024)
The importance of having engineering students proficient in visual literacy has long been recognized. Within this objective, the role of freehand drawing is paramount. It is, therefore, important to reinforce its practice for engineering communication and visual thinking support. This paper reports the findings of a research project aimed at studying the visual literacy skills of engineering students and the use of freehand drawing for this purpose. This exploratory study focuses on visualization and its externalization through freehand drawing. An empirical study was conducted with 66 engineering students from the Universidad Politécnica de Madrid (Spain). Their skills for expressing visualized images through freehand drawing and their tendency to use drawings for problem-solving were evaluated. The findings of the study indicate that students generally lack skills in expressing ideas through freehand drawing. Additionally, they do not tend to apply drawing when finding solutions to given problems. Considering the importance of freehand drawing to reinforce visual literacy, the implementation of its practice is encouraged in order to have students competent in thinking and communicating through these means.